1975
DOI: 10.1016/0014-2999(75)90305-2
|View full text |Cite
|
Sign up to set email alerts
|

α-Methylnoradrenaline induced hypotension and bradycardia after administration into the area of the nucleus tractus solitarii

Abstract: , a-Methylnoradrenaline induced hypotension and bradycardia after administration into the area of the nucleus tractus solitarii, European J. Pharmacol. 32 (1975) 361--364.Bilateral injeetions of a-methylnoradrenaline into the area of the nucleus tractus solitarii of the brain stem caused a dose-dependent decrease of systemic arterial blood pressure and heart rate of anesthetized rats. The effects were prevented and even reversed by a preceding injection of the a-adrenoceptor blocking agent phentolamine. Press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This contention is supported by the findings of others obtained in anesthetized animals that reflex bradycardia produced by elevation of arterial pressure is facilitated by the intracisternal administration of clonidine, an a-adrenergic agonist, 34 ' 35 that norepinephrine injected directly into NTS acutely and transiently lowers blood pressure and HR (an effect, blocked by a-adrenergic antagonists), 7 and that the depressor effects of a-methylnorepinephrine is mediated, in part, through a-adrenergic receptors within the NTS itself. 36 Although we failed to obtain chronic changes in HR following microinjection of 6-OHDA into the NTS, others have noted that the injection of norepinephrine directly into NTS produces bradycardia. 7 Since we have not directly injected norepinephrine into the NTS, we can only speculate as to the reasons for the discrepancy between our results and those of others.…”
Section: Discussionmentioning
confidence: 65%
“…This contention is supported by the findings of others obtained in anesthetized animals that reflex bradycardia produced by elevation of arterial pressure is facilitated by the intracisternal administration of clonidine, an a-adrenergic agonist, 34 ' 35 that norepinephrine injected directly into NTS acutely and transiently lowers blood pressure and HR (an effect, blocked by a-adrenergic antagonists), 7 and that the depressor effects of a-methylnorepinephrine is mediated, in part, through a-adrenergic receptors within the NTS itself. 36 Although we failed to obtain chronic changes in HR following microinjection of 6-OHDA into the NTS, others have noted that the injection of norepinephrine directly into NTS produces bradycardia. 7 Since we have not directly injected norepinephrine into the NTS, we can only speculate as to the reasons for the discrepancy between our results and those of others.…”
Section: Discussionmentioning
confidence: 65%
“…This nucleus, which receives the major part of the afferent sino-aortic baroreceptor fibres (see Palkovits and Zfiborszky, 1977), is densely innervated by catecholaminergic terminals and contains catecholaminergic cell bodies (DahlstrSm and Fuxe, 1964;Fuxe, 1965;Palkovits and Jacobowitz, 1974). Previous studies showed that local bilateral application of adrenaline, noradrenaline and a-methylnoradrenaline in the NTS caused a decrease of blood pressure and heart rate (De Jong, 1974;Nijkamp and De Jong, 1975;De Jong and Nijkamp, 1976). The A2-region (described by DahlstrSm and Fuxe 1964) was the part of the NTS in which injections of a-methylnoradrenaline were found to be most effective (Zandberg and De Jong, 1977a).…”
Section: Introductionmentioning
confidence: 99%
“…The antihypertensive substance a-methyldopa reduces blood pressure after neuronal uptake and metabolization to amethylnoradrenaline, an c2-adrenoceptor agonist, by a centrally mediated effect on the autonomic nervous system (for review see Henning, 1984). The X2-receptors, that are stimulated by a-methylnoradrenaline, are presumably located in the nucleus tractus solitarii (NTS) (Nijkamp & De Jong, 1975;De Jong & Nijkamp, 1976).…”
Section: Introductionmentioning
confidence: 99%